2019
DOI: 10.1016/j.seizure.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term seizure-free outcomes of dietary treatment in infants according to etiology

Abstract: It is important to determine whether specific etiology is more effective to dietary treatment so that the diet can be started earlier for infants. We evaluated etiology-specific, seizure-free outcomes of dietary treatment in infants < 1 year of age. Methods: We conducted a 10-year, retrospective, longitudinal observational study of 115 infants treated with ketogenic diet (KD) or modified Atkins diet (MAD). Results: Most patients (70%) received classical KD; 30% received MAD. During follow-up, 90%, 73%, and 61%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…In the past, KDTs were not recommended for infants because infancy is a critical period for neurodevelopment and due to the perceived risk of inadequate nutrition [ 39 ]. Compared with adults, neonates and infants have the advantage of having a metabolism associated with the use of ketone bodies [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the past, KDTs were not recommended for infants because infancy is a critical period for neurodevelopment and due to the perceived risk of inadequate nutrition [ 39 ]. Compared with adults, neonates and infants have the advantage of having a metabolism associated with the use of ketone bodies [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, infancy and neonatal age represent a target population as "fragile" as promising for the use of KD. In a 10-year, retrospective, observational study involving 115 infants treated with KD (70%) or MAD (30%), the authors found a high rate of long-term seizure-free outcomes (37% of the patients at 12 months), which can be predicted based on the seizure freedom at three months (50% of the patients) regardless of etiology (genetic, structural brain abnormalities, and metabolic pathologies) [118]. In fact, the higher amounts of enzymes that metabolize ketones and the production of monocarboxylic acid transporters, leading to more ketone bodies that can cross the blood-brain barrier, are responsible for the greater efficacy of such dietary treatment in infants.…”
Section: Variation Of Ketogenic Diet Regimen Per Age Groupmentioning
confidence: 99%
“…At that time, 10 retrospective studies including 32 children and adults with RSE showed dramatic beneficial effects of stable at long-term follow-up. Another study reports specific etiologic differences in long-term seizure-free outcomes among 115 patients who initiated KDTs before 1 year of age and shows that seizure freedom within the first 3 months could be a predictor of long-term seizure freedom [55]. A similar study including 109 patients with RE under 3 years of age with different etiologies reports that patients with a genetic etiology were particularly good responders to KDTs [54], with nearly half of patients with a confirmed genetic abnormality showing more than a 50% reduction in seizure frequency.…”
Section: Use Of Kdts For Status Epilepticusmentioning
confidence: 99%
“…Contrary to a conventional view, under 2 years of age may be the optimum time to initiate a KDT because of the metabolic advantages of infants [50][51][52][53][54][55]. Numerous studies provide evidence for the advantages of using KDTs in infants with RE.…”
Section: Use Of Kdts For Infants With Rementioning
confidence: 99%